2018
DOI: 10.1063/1.5019454
|View full text |Cite
|
Sign up to set email alerts
|

A Kirkwood-Buff derived force field for alkaline earth halide salts

Abstract: The activity and function of many macromolecules in cellular environments are coupled with the binding of divalent ions such as calcium or magnesium. In principle, computer simulations can be used to understand the molecular level aspects of how many important macromolecules interact with ions. However, most of the force fields currently available often fail to accurately reproduce the properties of divalent ions in aqueous environments. Here we develop classical non-polarizable force fields for the aqueous al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 92 publications
(134 reference statements)
0
25
0
Order By: Relevance
“…There are reasons as to why the ever-accelerating CPU speed and some potentially gamechanging innovations in free-energy calculations [45] still have not made solubility prediction a relic of the past. Simulations of the liquid state still have to rely on classical molecular dynamics requiring force field parameterization, which is still a matter of active research even for the most common cosolvents (such as urea) for aqueous solutions [46,47].…”
Section: A Meeting Point Between Experiments and Simulations Is Provimentioning
confidence: 99%
“…There are reasons as to why the ever-accelerating CPU speed and some potentially gamechanging innovations in free-energy calculations [45] still have not made solubility prediction a relic of the past. Simulations of the liquid state still have to rely on classical molecular dynamics requiring force field parameterization, which is still a matter of active research even for the most common cosolvents (such as urea) for aqueous solutions [46,47].…”
Section: A Meeting Point Between Experiments and Simulations Is Provimentioning
confidence: 99%
“…For a case of Ca 2+ ion we also performed a classical simulation of one molecule of CaCl 2 in a 99.8 Å box of water, the force field parameters were taken from ref. 68. The simulation step was 2 fs, the temperature of 300 K was controlled by the v-rescale thermostat with coupling time 0.1 ps, the pressure of 1 bar was controlled by the Parrinello-Rahman barostat with coupling time of 2 ps.…”
Section: Ensemble Cluster-continuum Approachmentioning
confidence: 99%
“…KB integrals can be used for the development and parameterization of force fields [61,108,109]. Weerasinghe and Smith provide KB derived force fields (KBFF) for a number of mixtures such as, sodium chloride in water [108], urea and water [110], acetone and water [111], and methanol and water [112].…”
Section: Other Applicationsmentioning
confidence: 99%
“…The authors of Refs. [61,108,109] found that macroscopic properties can be accurately computed using the KBFF models, while addressing solute-solute and solvent-solute molecular structure of the systems considered. For instance, in Ref.…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation